Improving Students Reading Fluency through Audiobooks in Remote Learning - Indra Pratiwi; Akhdiyatul Akhdiyatul; Nur Aida (Yayasan Pendidikan Bima Berilmu, 2022)
Due to the Covid-19 pandemic, the teaching and learning process has become more challenging and stressful. Students are expected to do self-learning without being directly guided when attending the class is not possible, while the teachers must keep encouraging the students to learn independently. At the same time, the teachers also have to think about alternative methods and materials for remote learning. Especially for those teachers who teach EFL students, they have to figure out certain materials that meet students' needs and the most relaxing activities that fit students learning styles so that the students can learn independently without feeling bored. Therefore, this study aims to investigate the implementation of audiobooks to foster students' performance in English, especially in reading fluency during remote learning. This study represents Action Research that employs quantitative and qualitative types of data. It is done in the form of cycles adapted from the Action Research cyclical process (from Mertler, 2012b). The result of this study showed that audiobook has a favourable implication on the student's ability to be more fluent in reading and positively influences students' attitudes toward their experience with the audiobook.